FBM courtesy visit to the chairman of UiTM's Board of Directors - UiTM, Faculty of Business and Management (UiTM, 2023)
The Faculty of Business and Management (FBM) paid a courtesy visit to Emeritus Prof. Datuk Dr. Raduan Che Rose, the Chairman of UiTM's Board of Directors. The delegation was composed of Prof. Dr. Firdaus Abdullah (Dean of FBM) and Prof. Dr. Rugayah Hashim, Ts. Dr. Ahmad Rais Mohamad Mokhtar, and Dato' Dania Abdul Wahab and Prof. (Adj.) Dr. Behrang Parhizkar from ChamRun Digital, a key business partner. The central topic of discussion revolved around a proposition for Digital Skills Training with the objective of cultivating a digital society that empowers the citizens of Malaysia. The suggested project has the objective of creating cutting-edge technologies and promoting cooperation across different sectors. These efforts will contribute to improving connection, understanding, accessibility, and inclusion within the digital society of Malaysia.